Social Forestry and Dairy Farming Practices in West Java With Special Emphasis on the Examination of Conflict Identification and Resolution - Rusvi, Gamma Galudra Triana (2003)
The objective of this study was to determine the types of conflicts between dairy farming and social forestry programs in two selected villages in Lembang, West Java, Indonesia, and make recommendation on how to resolve it. Three stakeholders were involved in this conflict, namely, dairy farmers, social forestry participants, and State Forest Corporation (SFC). In order to understand the conflicts, the study surveyed the socio-economic conditions of the dairy farmers and social forestry participants, examined the dairy farming and social forestry practices by selected dairy farmers and social forestry participants. A questionnaire survey was carried in 2001 out on a random sample of 158 dairy farmers and on a purposive sample of 60 social forestry participants. In addition, data were also gathered from five purposively selected SFC officials. Conflicts were found to exist and persist between actors as well among the members of the actors. Competition for land and forages were the sources of conflicts between the dairy farmers and social forestry participants. Among the social forestry participants themselves, conflicts arose in the course of obtaining tumpangsari sites as well as tumpangsari plots. Conflicts between SFC officials and dairy farmers revolve around the issues of the use of state forestland by the agriculture farmers and the scope of social forestry program which pays a lot attention on agriculture plantation. The paternalistic attitude of the SFC officials as well as their underestimation of the capacity of the social forestry participants has often created conflicts between the two groups of actors. Conflicts between the two actors have also taken place due to divergence in their interests as well as the limited management rights given to the social forestry participants. Based on the experience of other social forestry program in Java, conflicts among the social forestry participants for tumpangsari sites and plots could be resolved by means of a lottery system and lengthening the tumpangsari period. In order to resolve the conflicts between the dairy farmers and the social forestry participants, it is recommended that both parties meet and discuss in a negotiation process. One important aspect of the negotiation is the SFC officials must recognize the rights of access of the dairy farmers to the state forestland.